Menopausal depressions – atypical course, treatment - Krogulski, Sławomir; Lipińska-Szałek, Agata (Menopause Review/Przegląd Menopauzalny, 2004)
Depression, considered as an illness demanding a medical treatment, is a common case in a woman’s menopausal period. The discussion which in scientific literature has lasted for years refers to: etiology and pathogenesis of the depressive syndromes of this period, their features distinctive from other affective diseases, and problems connected with a proper classification and terminology. In this discussion the specific features of the symptoms, and the atypical course of the climacteric depression are raised. In a treatment of this kind of depression a requirement to consider specific biological, psychological, and psycho-social conditions of the climacteric period is emphasized. This article is an attempt of organizing knowledge concerned to the above-mentioned subjects.